Analysis of appointment of honorary teachers to be prospective government services with work agreements (PPPK) in Bantaeng District - Nova Srikanti (Central Research Institute for Agriculture (CeRIA), 2021)
The purpose of this study was to find out the implementation of the appointment of honorary teachers to become government employee candidates with work agreements in Bantaeng Regency. This research was conducted using qualitative methods. From the use of qualitative methods. Collecting data using interviews, observation, and documentation. This research was conducted at the Education and Culture Office of Bantaeng Regency. The informants of this research were 5 people. The results showed that the process of appointing honorary workers to become government employee candidates with work agreements (PPPK) in Bantaeng Regency had been carried out well, in accordance with the indicators described by the researchers, namely identifying vacant positions, seeking position information through job analysis, determining candidates right, start working. Where the appointment process has been carried out in accordance with government regulations, although the results of this appointment have not been able to drastically reduce honorary workers.